Effect of granular activated carbon pore-size distribution on biological activated carbon filter performance. (15th June 2020) - Lu, Zedong; Sun, Wenjun; Li, Chen; Cao, Wenfeng; Jing, Zibo; Li, Simiao; Ao, Xiuwei; Chen, Chao; Liu, Shuming
Abstract: Proper granular activated carbon (GAC) selection could improve the performance of biological activated carbon (BAC) filters through a combination of adsorption and biodegradation, while the GACs used in BAC filters are now mainly selected according to adsorption function, ignoring biodegradation. In this study, sand filter effluent obtained from a drinking water treatment plant was fed into continuous-flow bench-scale BAC columns operated in parallel over 245 days to examine the effects of GAC pore-size distribution on BAC filter performance, in terms of the dissolved organic carbon (DOC) and disinfection byproduct (DBP) precursors. A metagenomic analysis indicated that bacterial community structure played an important role in BAC filter performance. A significant correlation was found between metabolism-related proteins and the volume of micro-level macropores based on metaproteomic analysis. It is suggested that the adsorption saturation was dynamic and that adsorption played a role in the performance of the BAC filters throughout the 245-day operating period. Renewed adsorption capacity, or bioregeneration, was driven by bacterial metabolic activity. Such activity largely depended on the organic matter adsorbed by the GAC, in which micro-level macropores, especially those with diameters of 0.2–10 μm, played an important but previously unrecognized role. The results suggest that more attention should be paid to well-developed pores and pore-size distribution in the production and selection of GAC used for full-scale drinking water biofilters. Graphical abstract: Image 1 Highlights: Studied effect of pore-size distribution characteristics on BAC filter performance. Investigated BAC filter bacterial activity using metagenomics and metaproteomics. Indicators affecting BAC filter performance: micropores and micro-level macropores. Role of micro-level macropores in BAC filter was typically neglected.